Effect of irrigation and nitrogen management on water productivity and nutrient uptake of aerobic rice - Duary, Swarnali; Pramanik, Kalipada; Panda, Debasish (ORYZA-An International Journal of Rice, 2022)
Water and nitrogen fertilizer are the two important inputs for rice cultivation. A field experiment was carried out in split plot design, with three water management treatments, irrigation at (i) 75 % Cumulative Pan Evaporation (CPE), (ii) 100% CPE, (iii) 125% CPE in the main plot, and four nitrogen management strategies, (i) 100% nitrogen applied through chemical fertiliser, (ii) 75% through chemical fertiliser + 2.5 t ha-1 vermicompost, (iii) 50% through chemical fertiliser + 5.0 t ha-1 vermicompost, and (iv) 25% through chemical fertiliser +7.5 t ha-1vermicompost in subplot. The grain yield, straw yield, water productivity, nutrient uptake and economics of aerobic rice were considerably affected by irrigation and nitrogen management. Crops receiving irrigation at 125% CPE had the highest grain yield (3618 kg ha-1), which was comparable to crops receiving irrigation at 100 % CPE. Regardless of irrigation and nitrogen management, the straw yield of aerobic rice ranged from 4127 to 5092 kg ha-1. The highest total NPK uptake by grain was recorded with nitrogen at 100 % N through fertiliser (N1), which was significantly greater than what was obtained from other nitrogen treatments and irrigation management at 100 % CPE (I100) and 125 % CPE (I125) was significantly better than irrigation at 75 % CPE (I75). Irrigation management at 125 % CPE yielded the highest gross return, net return, and B: C ratio of aerobic rice, which was comparable to 100 % CPE and 100 % N through fertiliser, 75 % N through fertiliser + 2.5 t ha-1 vermicompost, and significantly higher than other nitrogen treatments.